Preoperative 18F-FDG-PET/CT vs Contrast-Enhanced CT to Identify Regional Nodal Metastasis among Patients with Head and Neck Squamous Cell Carcinoma. (September 2017) - Cho, Joshua K.; Ow, Thomas J.; Lee, Andrew Y.; Smith, Richard V.; Schlecht, Nicolas F.; Schiff, Bradley A.; Tassler, Andrew B.; Lin, Juan; Moadel, Renee M.; Valdivia, Ana; Abraham, Tony; Gulko, Edwin; et al.
Objective: Our objective was to compare the accuracy of preoperative positron emission tomography (PET)/computed tomography (CT) and contrast-enhanced CT (CECT) in detecting cervical nodal metastases in patients treated with neck dissection and to scrutinize the ability of each modality to determine nodal stage. Study Design: Case series with chart review. Setting: Montefiore Medical Center, Bronx, New York. Subjects and Methods: Patients who underwent neck dissection at our institution for primary treatment of head and neck squamous cell carcinoma (HNSCC) and had received preoperative PET/CT and CECT were included in this study. Imaging studies were reinterpreted by 3 specialists within the field and compared for interreader agreement. Concordance between radiology and histopathology was measured using neck levels and sides, along with patient nodal stage. Sensitivity, specificity, accuracy, positive predictive value, negative predictive value, and agreement coefficients were calculated. Results: Seventy-three patients were included in the study. Sensitivity was 0.69 and 0.94 (level and side) for PET/CT vs 0.53 and 0.66 for CECT ( P = .056, P = .001). Specificity was 0.86 and 0.56 for PET/CT vs 0.91 and 0.76 for CECT ( P = .014, P = .024). No significant difference was found in overall accuracy ( P = .33, P = .88). The overall agreement percentages between N stage called by imaging modality and pathology were 52% and 55% for PET/CT and CECT, respectively. Conclusion: No significant difference in sensitivity was found between PET/CT and CECT. CECT was found to have superior specificity compared with PET/CT. The information gleaned from each modality in the pretreatment evaluation of HNSCC appears to be complementary.